Religiosity and Risky Behaviors among Adolescents Living With HIV in Southwest Nigeria - Sodeinde, Kolawole; Akadri, Adebayo; Adepoju, Akinmade; Oluwole, Temitayo; Bamidele, Olabisi; Abiodun, Olumide (Journal of Religion and Public Health, 2024)
Risky behaviors remain highly prevalent among adolescents,and theyarethe foremost cause  of unplanned  pregnancies,  sexually  transmitted  infections  (STIs) including  HIV, intellectual  deterioration,  and  suicide  attempts.Religion  has  been  opined  tomitigate risky  behaviorsamong  young  people.This  study  assessed if  there  is  arelationship between   religiosity   and   risky   behaviors   among   adolescents   living   with   HIV   in southwest Nigeria. It is adescriptive cross-sectional study of 212 adolescents selected via   a   multistage   sampling   technique.   Data   were   collected   using   interviewer-administered  questionnaires. Religiosity  was  classified  as  low,  moderate,and  high religious involvement based on the frequency of religious activities attendance using the Duke  University  Religion  Index. Data  was  analyzed using  SPSS  version  22.  Logistic regression was used to find factors associated with risky behavior. P was set as < 0.05.Low religiosity (OR=23.975; 95% C.I=2.591-221.851), late adolescence (OR=10.404; 95% C.I = 2.259-47.918) and not having formal education (OR=3.558; 95% C.I=1.324-9.562)  significantly  predicted  high-risk  behavior. High  religiousinvolvementshold some promise in mitigating risky sexual behaviors among adolescents with HIV.Keywords: HIV/AIDS, Religiosity, Risky behavior.